Determinant Muslim People to Adopt Islamic Bank in Indonesia - Nursakina Nursakina; Junaidi Junaidi (LP3M Universitas Putra Bangsa, 2022)
Islamic banks play an important role as a facilitator in all economic activities in the halal industry ecosystem. The existence of the Islamic banking industry in Indonesia has experienced a significant increase and development in the past three decades. This study aims to analyze the lack of public interest in saving at Islamic banks in Palopo City. The analysis is based on several factors, namely profit sharing, service quality, customer satisfaction, and loyalty. This study uses primary data collected by giving questionnaires to the people of Palopo City, with a sample of 300 respondents. The method used is a quantitative method using primary data and a numerical scale (numbers). Based on the analysis that has been done, the results show that the variables of profit sharing, service quality, customer satisfaction, and loyalty have a significant and positive effect on the low interest of the people of Palopo City in saving in Islamic banks.